Pengaruh Profitabilitas, Leverage dan Intensitas Persediaan terhadap Perencanaan Pajak - Juwainah Ria; Nera Marinda Mahdar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to examine the influence of profitability, leverage, and corporate governance on tax planning. The independent variables used in this study are profitability, leverage, and inventory intensity. Meanwhile, the independent variable in this study is tax planning. The tax pre-planning in this study was measured by the Cashl Effectivel Tax Ratel (CETRl). The population in this study is lmanufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2021-2023 period. The determination of the sample in this study used the purposive sampling method. The results of the study show that profitability, leverage, and inventory intensity have a significant effect on tax planning.